Bifurcation of time crystals in driven and dissipative Rydberg atomic gas - Bang Liu; Li-Hua Zhang; Yu Ma; Qi-Feng Wang; Tian-Yu Han; Jun Zhang; Zheng-Yuan Zhang; Shi-Yao Shao; Qing Li; Han-Chao Chen; Guang-Can Guo; Dong-Sheng Ding; et al. (Nature Communications)
Abstract A time crystal is an exotic phase of matter where time-translational symmetry is broken; this phase differs from the spatial symmetry breaking induced in conventional crystals. Lots of experiments report the transition from a thermal equilibrium phase to a time crystal phase. However, there is no experimental method to probe the bifurcation effect of distinct continuous time crystals in quantum many-body systems. Here, in a driven and dissipative many-body Rydberg atom system, we observe multiple continuous dissipative time crystals and emergence of more complex temporal symmetries beyond the single time crystal phase. Bifurcation of time crystals in strongly interacting Rydberg atoms is observed; the process manifests as a transition from a time crystal of long periodicity to a time crystal of short periodicity, or vice versa. By manipulating the driving field parameters, we observe the time crystal’s bistability and a hysteresis loop. These investigations indicate new possibilities for control and manipulation of the temporal symmetries of non-equilibrium systems.